Advanced care planning as an organisational issue (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
The contribution examines shared care planning (SCP) as an organisational issue for the National Health System. The heterogeneity of the situations in which ACP can be elaborated is declined to identify some guidelines that can guide an organisational approach that promotes ACP in the various care settings, and that can be listed as follows: personalised pathways, staff training and information to citizens, adoption of internal organisational acts.
Keywords: Advance care planning; shared care planning; healthcare organization; essential levels of healthcare; professional training; communication